Nova ureditev denarnih socialnih pomoči - Strban, Grega (Delavci in delodajalci, 2011)
The legislature has reshaped the social assistance scheme with the two recently passed legislative acts. Some modifications improve the legal position of the social assistance recipient and his/her family. However, questions of defining family law notions in the field of social assistance, equalising the purpose of child benefit with the one of social assistance, permanently prohibiting the disposal of real estate, and abolishing categorical social assistance, are raised.
Keywords: državne pokojnine; pravna ureditev; socialna pomoč; socialna varnost; socialno pravo; socialno skrbstvo; socialno varstveni prejemki; spremembe; uveljavljanje pravic iz javnih sredstev; varstveni dodatek